Life Thinning and Gaming Disorder : A Longitudinal Qualitative Registered Report - Karhulahti Veli-Matti; Siutila Miia; Vahlo Jukka; Koskimaa Raine (Peer Community In, 2025)
The academic debates regarding the psychiatric relevance of gaming disorder continue largely because the lived experiences of treatment-seekers remain mostly unstudied. This registered report addresses the above research gap with a longitudinal design that pursues a comparative descriptive understanding of how intensive gaming experiences evolve in both clinical and non-clinical life situations. Accompanied by a rich health survey, interpretative phenomenological analysis was adapted to understand in-depth interview data from treatment-seeking (n=5) and esports-playing (n=4) participants, the latter of which did not experience any gaming-related health problems. The interviews were carried out as a 1-year follow-up. The study finds intensive relationships with gaming to be experienced through multidimensional cyclicality. For treatment-seekers, this manifests as a shift in problem processing that involves a search for new gaming and life meanings; meanwhile, for esports-playing participants, the meanings of gaming evolve and can rapidly adapt to unexpected life events. We propose life thinningand resilience integration processes as working models that can help better describe and theoretically explain how some individuals end up seeking gaming-related treatment, whereas for others gaming continues to be part of their identity and resilience. The findings call for more qualitative registered reports with treatment-seekers and other intensively gaming people from different cultures to better understand the spectrum of intensive gaming phenomenologically—and specifically, what it means for people to seek treatment for their gaming.